2023
DOI: 10.3390/met13030473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphite Morphology on the Thermomechanical Performance of Compacted Graphite Iron

Abstract: Compacted graphite iron (CGI) has gained significant attention in automotive industry applications thanks to its superior thermomechanical properties and competitive price. Its main fracture mechanism at the microscale—interfacial damage and debonding between graphite inclusions and a metallic matrix—can happen under high-temperature service conditions as a result of a mismatch in the coefficients of thermal expansion between the two phases of CGI. Macroscopic fracture in cast iron components can be initiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
1
3
0
4
Order By: Relevance
“…В процессе затвердевания чугуна способ роста графита и конечная морфология зависят от термодинамических условий и химического состава расплавленного чугуна. Согласно работам [8][9][10][11][12][13][14][15][16][17][18][19][26][27][28][29][30][31][32][33][34][35][36][37][38][39] механизм формирования морфологии графита в чугуне следующий. Когда расплавленное железо достаточно чистое и в нем отсутствуют поверхностно-активные элементы (O, S или другие примеси), основным направлением роста графита является нормаль базовой плоскости (0001) (направление c), и графит будет преимущественно развиваться через спиральный рост в сферическую форму, поскольку он может происходить с минимальной энергией активации [20,21].…”
Section: результаты и их обсуждениеunclassified
See 2 more Smart Citations
“…В процессе затвердевания чугуна способ роста графита и конечная морфология зависят от термодинамических условий и химического состава расплавленного чугуна. Согласно работам [8][9][10][11][12][13][14][15][16][17][18][19][26][27][28][29][30][31][32][33][34][35][36][37][38][39] механизм формирования морфологии графита в чугуне следующий. Когда расплавленное железо достаточно чистое и в нем отсутствуют поверхностно-активные элементы (O, S или другие примеси), основным направлением роста графита является нормаль базовой плоскости (0001) (направление c), и графит будет преимущественно развиваться через спиральный рост в сферическую форму, поскольку он может происходить с минимальной энергией активации [20,21].…”
Section: результаты и их обсуждениеunclassified
“…Тем не менее при анализе зарубежных и отечественных стандартов все подходы оценки субъективно изменяют форму графита от пластинчатой к узловатой с некоторыми более или менее вырожденными формами между ними. В работах [35][36][37][38] представлен новый подход к инструментальной оценке морфологических особенностей графита в процессе кристаллизации на основе термического анализа, совмещенного с оценкой расширения и сжатия при охлаждении. Механическая система расширения/ сжатия использовалась для оценки начального расширения чугунов, обработанных магнием, которое было идентифицировано как основной фактор, влияющий на чувствительность к усадке чугунов с различной морфологией графита [36].…”
Section: результаты и их обсуждениеunclassified
See 1 more Smart Citation
“…In the work of Muhond et al [8], some trace elements (S, B, Se) were observed to stabilise the flake or nodular growth morphology of graphite, while F, O, N, P failed to do so. In general, there are two main approaches used for modelling the mechanical behaviour of CGI: representative volume element (RVE) and unit cell [9][10][11][12]. To the best of the author's knowledge, these two approaches are widely used in the field of computational mechanics to simulate the fracture behaviours of heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, XFEM is usually used to predict the stress-strain behaviour without a predefined crack [9,10]. With its need for additional degrees of freedom, XFEM may require more computational resources, while In general, there are two main approaches used for modelling the mechanical behaviour of CGI: representative volume element (RVE) and unit cell [9][10][11][12]. To the best of the author's knowledge, these two approaches are widely used in the field of computational mechanics to simulate the fracture behaviours of heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%